Development and growth of the pelvic fin in the extant coelacanth Latimeria chalumnae. Issue 3 (9th June 2020) - Mansuit, Rohan; Clément, Gaël; Herrel, Anthony; Dutel, Hugo; Tafforeau, Paul; Santin, Mathieu D.; Herbin, Marc
Abstract: The ontogeny of the paired appendages has been extensively studied in lungfishes and tetrapods, but remains poorly known in coelacanths. Recent work has shed light on the anatomy and development of the pectoral fin in Latimeria chalumnae . Yet, information on the development of the pelvic fin and girdle is still lacking. Here, we described the development of the pelvic fin and girdle in Latimeria chalumnae based on 3D reconstructions generated from conventional and X‐ray synchrotron microtomography, as well as MRI acquisitions. As in other jawed vertebrates, the development of the pelvic fin occurs later than that of the pectoral fin in Latimeria . Many elements of the endoskeleton are not yet formed at the earliest stage sampled. The four mesomeres are already formed in the fetus, but only the most proximal radial elements (preaxial radial 0–1) are formed and individualized at this stage. We suggest that all the preaxial radial elements in the pelvic and pectoral fin of Latimeria are formed through the fragmentation of the mesomeres. We document the progressive ossification of the pelvic girdle, and the presence of a trabecular system in the adult. This trabecular system likely reinforces the cartilaginous girdle to resist the muscle forces exerted during locomotion. Finally, the presence of a preaxial element in contact with the pelvic girdle from the earliest stage of development onward questions the mono‐basal condition of the pelvic fin in Latimeria . However, the particular shape of the mesomeres may explain the presence of this element in contact with the girdle.